Associação entre disfunção autonômica esofágica e cardíaca na doença de Chagas - Sandra Monetti Dumont Sanches (2024)
Chagas disease (Chd) is a neglected tropical disease that has a variable clinical course and can manifest in indeterminate (IF), cardiac, digestive, or cardio-digestive forms. The most prevalent determined form is chronic chagasic cardiomyopathy (CCC), characterized by by progressive ventricular dysfunction, complex arrhythmia and sudden death, linked to autonomic dysfunction, among other mechanisms. Esophageal dysfunction may be an indirect marker of enteric autonomic impairment observed in the digestive form. We aimed to evaluate the possible association between esophageal and cardiac autonomic denervation in indeterminate and CCC forms. Sixty-one patients with a serological diagnosis of Chd were grouped into IF (28) and CCC (33), 54,1% women, mean age 57 years, submitted to esophageal scintigraphy and esophageal transit time (ETT) and percentage of esophageal emptying (%EE) were recorded. Patients also underwent 24-hour Holter monitoring and heart rate variability (HRV) indices and ventricular extrasystole (VES) burden were reviewed by a cardiologist. The correlation between TTE, %EE, and HRV (SDNN - standard deviation of mean normal RR intervals, HFP - high-frequency power, LFP - low-frequency power), in addition to ESV in 24 hours were analyzed with IBM SPSS 23 software. The left ventricular ejection fraction was lower in the CCC group (44,0 ± 10,8 vs. 65,6 ± 5,7, p<0,001). Autonomic dysfunction showed a distinct pattern between IF and CCC, with lower SDNN andLF/HF values in the CCC group (100,0 ± 49,9 vs. 124,4 ± 43,9, p=0,049 e 1,4 (0,9 - 2,2) vs. 4,7 (1, 7 - 9,6), p<0,001, respectively). The CCM group also had higher 24h VES values 890,0 (120,0 - 2743,0) vs. 44,5 (1,2 3 228,7), p<0,001. There was significant inverse correlation between ETT and (ß=- 0,474, p<0,001), LFP (ms²) (ß=- 0,272, p=0,036), HFP (ms²) (ß=-0,363, p=0,004) and LH/FH (ß=-0,321, p=0,012) in the total sample. There was also a statistically significant and direct correlation between ETT and VES (ß=0,573, p=0,001) in the total sample. In conclusion, Chd patients with greater esophageal dysmotility showed a decrease in the oscillatory components of HRV and greater arrhythmic density, possibly as a result of more severe sympathetic and parasympathetic cardiac denervation.